1992
DOI: 10.1111/j.1365-2621.1992.tb14337.x
|View full text |Cite
|
Sign up to set email alerts
|

Snap Bean Quality Changed Minimally When Stored in Low Density Polyolefin Film Package

Abstract: Snap beans packed in low density polyolefin film and stored at 5°C and 10°C were removed at days 0, 4, 8, 12, and 16 for quality evaluation. Chlorophyll content of beans stored at 5°C was not influenced by storage period. Pods stored at 10°C showed significant increase in chlorophyll after 4 days storage followed by a decline as time of storage increased. Hue angle and tristimulus a* corresponded more closely to chlorophyll content and were better indicators of snap bean color than chroma and tristimulus L* an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…those of snap bean (Phaseolus vulgaris L.). 21 TA ranged between 1.7 and 2.8 g malic acid kg −1 FW, which is also comparable to the values reported for snap bean. 22 Unlike the size characteristics of pods (weight and length), the determinations of TSSC and TA did not show any consistent differences between the accessions of ssp.…”
Section: Suitable Stage For Harvesting and Pod Morphological Charactesupporting
confidence: 88%
See 1 more Smart Citation
“…those of snap bean (Phaseolus vulgaris L.). 21 TA ranged between 1.7 and 2.8 g malic acid kg −1 FW, which is also comparable to the values reported for snap bean. 22 Unlike the size characteristics of pods (weight and length), the determinations of TSSC and TA did not show any consistent differences between the accessions of ssp.…”
Section: Suitable Stage For Harvesting and Pod Morphological Charactesupporting
confidence: 88%
“…TSSC (Fig. ) exceeded 5 °Brix in all accessions and in some cases reached 6.5 °Brix (Cp 4877, Vg59, AUA2) and even 7.6 °Brix (Cp 5647) – values comparable to those of snap bean ( Phaseolus vulgaris L.) . TA ranged between 1.7 and 2.8 g malic acid kg −1 FW, which is also comparable to the values reported for snap bean .…”
Section: Resultssupporting
confidence: 57%
“…Although superficial color intensity is dependent on the snap bean cultivar and maturity of the pod at harvest (Mayland and Dean, 1971), increasing the storage time and temperature often results in loss of brightness and greenness and increased yellowing. Trail et al (1992) also reported that after 8 d, snap beans stored at 10°C were lighter (higher L*) than pods stored at 5°C, but after 16 d, lightness of the pods stored at 5°C increased significantly compared with days 4 and 8. After 16 d, hue and chroma of snap beans stored at either 5 or 10°C decreased significantly indicating a loss of greenness and brightness of the pods (Trail et al, 1992).…”
Section: Resultsmentioning
confidence: 89%
“…Quality differentiation among individual fruits and vegetables by consumers is based primarily on appearance (Zind, 1989). In snap beans, color is an important feature, which changes from a desirable bright green to an objectionable yellowish color (Trail et al, 1992). Textural attributes and loss of chlorophylls are also excellent indices of quality because they parallel color changes, loss of ascorbic acid, and offflavor development (Cain et al, 1953;Martinez et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation